2008
DOI: 10.1111/j.1365-2672.2008.03840.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sampling tools for environmental sampling of bacterial endospores from porous and nonporous surfaces

Abstract: Aims:  Having and executing a well‐defined and validated sampling protocol is critical following a purposeful release of a biological agent for response and recovery activities, for clinical and epidemiological analysis and for forensic purposes. The objective of this study was to address the need for validated sampling and analysis methods called out by the General Accounting Office and others to systematically compare the collection efficiency of various swabs and wipes for collection of bacterial endospores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…A Government Accountability Office (GAO) investigation following the 2001 anthrax incident concluded that validated sampling methods and statistical sampling designs were needed to provide confidence that there is no contamination when all sample results are negative (17, 18). This conclusion strongly reinforces the need for validated sampling methods to effectively respond to biothreats and ensure public safety.Following the 2001 anthrax incident, several research teams developed and investigated (in laboratory studies) the performance of sampling methods using swab, wipe, and vacuum collection devices for Bacillus anthracis or surrogate contaminants on different surfaces (1,2,3,4,5,6,7,13,14,15,16,22,23,25,28,34,38,40,44,45). In addition, the CDC has conducted formal validation studies on two methods for sampling nonporous surfaces: macrofoam swabs (23) and cellulose sponge wipes (39).…”
mentioning
confidence: 99%
“…A Government Accountability Office (GAO) investigation following the 2001 anthrax incident concluded that validated sampling methods and statistical sampling designs were needed to provide confidence that there is no contamination when all sample results are negative (17, 18). This conclusion strongly reinforces the need for validated sampling methods to effectively respond to biothreats and ensure public safety.Following the 2001 anthrax incident, several research teams developed and investigated (in laboratory studies) the performance of sampling methods using swab, wipe, and vacuum collection devices for Bacillus anthracis or surrogate contaminants on different surfaces (1,2,3,4,5,6,7,13,14,15,16,22,23,25,28,34,38,40,44,45). In addition, the CDC has conducted formal validation studies on two methods for sampling nonporous surfaces: macrofoam swabs (23) and cellulose sponge wipes (39).…”
mentioning
confidence: 99%
“…Preliminary investigations were conducted to select the optimum swab type and the optimum processing method (10,11,16). Others have evaluated the efficiency of various swab types for conducting surface sampling and processing methods for the swabs (1,4,8,15,19). However, using a swab to sample an area larger than 25.8 cm 2 may result in reduced recovery efficiency, so an alternative device for sampling of larger surface areas is needed.…”
mentioning
confidence: 99%
“…However, using a swab to sample an area larger than 25.8 cm 2 may result in reduced recovery efficiency, so an alternative device for sampling of larger surface areas is needed. Though other researchers have evaluated the efficiency of gauze wipes (2,7,19), a foam spatula (14), or the Biological Sampling Kit (BiSKit; Quicksilver Analytics, Inc., Abingdon, MD) (3) for sampling of B. anthracis or surrogates for B. anthracis from larger surface areas, none of these methods were evaluated to the extent required to provide a validated method. No acceptance criteria for environmental sampling currently exist; hence, one goal of this study was to investigate the variability of the method and establish acceptable limits for environmental sampling and processing protocols.…”
mentioning
confidence: 99%
“…As a result, over the last decade needs for quantitative assessment capabilities have driven research on the relative effectiveness of different sampling processes as well as the development of validated surface sampling and sample processing methods (27,49). Notably, the vast majority of these studies have utilized B. anthracis spores (13,20,23,27,28,48) or spores of a surrogate organism (4,5,8,9,18,58). Comparatively little effort has been applied in recent years toward improved surface sampling of viruses (31) and vegetative bacterial cells that represent likely biothreat (BT) agents (or surrogates thereof) (7,29,39,60).…”
mentioning
confidence: 99%